2009
DOI: 10.1161/strokeaha.108.538470
|View full text |Cite
|
Sign up to set email alerts
|

Green and Black Tea Consumption and Risk of Stroke

Abstract: Background and Purpose-Experimental models of stroke provide consistent evidence of smaller stroke volumes in animals ingesting tea components or tea extracts. To assess whether a similar association of black or green tea consumption with reduced risk is evident in human populations, we sought to identify and summarize all human clinical and observational data on tea and stroke. Methods-We searched PubMed and Web of Science for all studies on stroke and tea consumption in humans with original data, including e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(176 citation statements)
references
References 49 publications
9
166
1
Order By: Relevance
“…It has been found that green tea consumption is significantly associated with a lower risk of mortality due to stroke [29] and pneumonia [30] and imparts a lower risk of cognitive impairment [31], depression [32], and psychological distress [33]. These results have been confirmed by other researchers [34][35][36][37]. In addition, other epidemiologic studies have indicated that green tea consumption is associated with a lower risk of osteoporosis [38,39], and randomized placebo-controlled trials have indicated that green tea is effective in lowering cardiovascular risk factors [40,41].…”
Section: The Health Effects Of Green Teasupporting
confidence: 63%
“…It has been found that green tea consumption is significantly associated with a lower risk of mortality due to stroke [29] and pneumonia [30] and imparts a lower risk of cognitive impairment [31], depression [32], and psychological distress [33]. These results have been confirmed by other researchers [34][35][36][37]. In addition, other epidemiologic studies have indicated that green tea consumption is associated with a lower risk of osteoporosis [38,39], and randomized placebo-controlled trials have indicated that green tea is effective in lowering cardiovascular risk factors [40,41].…”
Section: The Health Effects Of Green Teasupporting
confidence: 63%
“…In 2016, 17.6 million deaths were caused by CVD; the death from cardiovascular diseases increased by 14.5% from 2006 and 2016 1. Previous epidemiological studies suggest that greater tea consumption is related to lower cardiovascular disease (CVD) risk2, 3; 1 to 3 or more cups of green or black tea per day is associated with a 20% to 30% risk reduction in stroke and CVD 3, 4. Produced from Camellia sinensis and rich in polyphenols and catechins, green and black tea were reported to exert a cardioprotective effect via antioxidation of proteins, DNAs, and lipids; antiproliferation of vascular smooth muscle cell; anti‐inflammation in cardiovascular cells; and improvement in endothelial functions, blood pressure,5 and lipid profile 6…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses have shown that consumption of flavonoid-rich foods are associated with reduced 28 risk of cause-specific mortalities such as those attributable to cancer, diabetes, and 29 cardiovascular disease [4][5][6][7] . Much of the beneficial effects of these foods have been attributed to 30 their high content of biologically active flavonoids, which have been shown to improve nitric 31 oxide homeostasis and endothelial function, and reduce platelet aggregation and oxidative 32 stress [8][9][10][11][12][13] .…”
Section: Introduction 23mentioning
confidence: 99%